Multimodal Magnetic Resonance Imaging Depicts Widespread and Subregion Specific Anomalies in the Thalamus of Early-Psychosis and Chronic Schizophrenia Patients. (6th September 2022) - Alemán-Gómez, Yasser; Baumgartner, Thomas; Klauser, Paul; Cleusix, Martine; Jenni, Raoul; Hagmann, Patric; Conus, Philippe; Do, Kim Q; Bach Cuadra, Meritxell; Baumann, Philipp S; Steullet, Pascal
Abstract: Background and Hypothesis: Although the thalamus has a central role in schizophrenia pathophysiology, contributing to sensory, cognitive, and sleep alterations, the nature and dynamics of the alterations occurring within this structure remain largely elusive. Using a multimodal magnetic resonance imaging (MRI) approach, we examined whether anomalies: (1) differ across thalamic subregions/nuclei, (2) are already present in the early phase of psychosis (EP), and (3) worsen in chronic schizophrenia (SCHZ). Study Design: T1-weighted and diffusion-weighted images were analyzed to estimate gray matter concentration (GMC) and microstructural parameters obtained from the spherical mean technique (intra-neurite volume fraction [VFINTRA )], intra-neurite diffusivity [DIFFINTRA ], extra-neurite mean diffusivity [MDEXTRA ], extra-neurite transversal diffusivity [TDEXTRA ]) within 7 thalamic subregions. Results: Compared to age-matched controls, the thalamus of EP patients displays previously unreported widespread microstructural alterations (VFINTRA decrease, TDEXTRA increase) that are associated with similar alterations in the whole brain white matter, suggesting altered integrity of white matter fiber tracts in the thalamus. In both patient groups, we also observed more localized and heterogenous changes (either GMC decrease, MDEXTRA increase, or DIFFINTRA decrease) in mediodorsal, posterior, and ventral anterior parts of the thalamus in both patient groups, suggesting that the nature of the alterations varies across subregions. GMC and DIFFINTRA in the whole thalamus correlate with global functioning, while DIFFINTRA in the subregion encompassing the medial pulvinar is significantly associated with negative symptoms in SCHZ. Conclusion: Our data reveals both widespread and more localized thalamic anomalies that are already present in the early phase of psychosis.